2021
DOI: 10.3389/fpubh.2021.718910
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Health Expenditure Associated With Frailty in Community-Dwelling Chinese Older Adults: A Prospective Cohort Analysis

Abstract: Background: Catastrophic health expenditure (CHE) represents a key indicator for excessive financial burden due to out-of-pocket (OOP) healthcare costs, which could push the household into poverty and is highly pronounced in households with members at an advanced age. Previous studies have been devoted to understanding the determinants for CHE, yet little evidence exists on its association with frailty, an important geriatric syndrome attracting growing recognition. We thus aim to examine the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…Noticeably, frailty is characterised as systemic, dynamic, and reversible. 4,12 Thus, certain intervention measures can be taken to prevent early occurrence of frailty, control its progress, or promote recovery to potentially lead to cost savings. This can provide policy makers with clear evidence of the 364 requirement for certain interventions to prevent and control frailty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noticeably, frailty is characterised as systemic, dynamic, and reversible. 4,12 Thus, certain intervention measures can be taken to prevent early occurrence of frailty, control its progress, or promote recovery to potentially lead to cost savings. This can provide policy makers with clear evidence of the 364 requirement for certain interventions to prevent and control frailty.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Jin et al examined the association between frailty and healthcare expenditure among Chinese older adults, and found that frailty was associated with higher odds of incurring outpatient, inpatient, and self-treatment expenditure. 11 Fan et al found that prefrail or frail adults were associated with higher odds for CHE through a prospective cohort analysis 12 in one of the first studies to explore the association between frailty and CHE in China. However, the study period was relatively short (2011)(2012)(2013).…”
Section: Introductionmentioning
confidence: 99%
“…Increased healthcare needs coupled with nancial dependency pushes the families of the elderly into catastrophe [16,17,18]. Fan et al [19] estimated that the incidence of catastrophic health expenditure (CHE) increased to 27 per cent in 2013 from 22 per cent in 2011 for the elderly in China. It is also found that elderly people suffering from non-communicable diseases are more exposed to CHE even with advanced risk pooling mechanism [17].…”
Section: Introductionmentioning
confidence: 99%
“…Using validated tools to identify pre-frail/frail older people is an essential step in estimating the community need and hence the formulation of preventative services [16][17][18]. Various frailty screening tools are available, but no tool has been developed for the Asia-Pacific region [12,14].…”
Section: Introductionmentioning
confidence: 99%